Ethno-medicinal plants used for herbal medication of jaundice by the indigenous community of Tripura, India - DIPANKAR DEB; B.K. DATTA; JABA DEBBARMA; SOURABH DEB (Society for Indonesian Biodiversity, 2016)
Deb D, Datta BK, Debbarma J, Deb S. 2016. Ethno-medicinal plants used for herbal medication of jaundice by the indigenous community of Tripura, India. Biodiversitas 17: 256-269. The immemorial association of medicinal plants is highlighted in various utilization pattern by different indigenous community. An investigation was done for less known ethno-medicinal plants used for jaundice as well as some other ailments by the indigenous community of Tripura, Northeast India. The traditional utilization of plants for treatment of jaundice by the indigenous communities is not so well studied in the land locked hilly part of the country. Timely ethnobotanical survey was undertaken with the knowledge of the species mainly used for curing jaundice. Necessary specimens were collected and cross-checked with the existing literatures. A total of 50 ethno-medicinal plant species belonging to 37 families were documented used for the treatment of jaundice (5 plant species with an additional ingredient of 5 species) and other diseases. Mainly leaves and roots were preferred to prepare decoction, pills and paste etc. Most of the plant species are sources of different chemical constituents which further contribute in formulating drug for common use. The active biochemical compounds are investigated by thorough literature survey. There is need for further critical phytochemical analysis and investigation of new valid drugs. Immediate documentation of such valuable knowledge is necessary as we are gradually missing many precious traditional herbal formulations with increasing impacts of modernization.